2023
DOI: 10.1097/wco.0000000000001138
|View full text |Cite
|
Sign up to set email alerts
|

Emerging approaches in neurostimulation for epilepsy

Abstract: Purpose of reviewNeurostimulation is a quickly growing treatment approach for epilepsy patients. We summarize recent approaches to provide a perspective on the future of neurostimulation.Recent findingsInvasive stimulation for treatment of focal epilepsy includes vagus nerve stimulation, responsive neurostimulation of the cortex and deep brain stimulation of the anterior nucleus of the thalamus. A wide range of other targets have been considered, including centromedian, central lateral and pulvinar thalamic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…22,24 In patients receiving RNS, the complication profile included surgical site infections which rarely led to device explantations or permanent neurologic consequences. 25-28 Similar results were also found in patients receiving VNS, where the total complication risk amounted to 3.7% with most being infections, hematomas, and vocal cord palsies. 29 In patients who underwent open resection, as determined by a nationwide study on over 6000 patients, a 30-day mortality rate of 3.4% and a complication rate of 17.9% were recorded.…”
Section: Discussionsupporting
confidence: 63%
“…22,24 In patients receiving RNS, the complication profile included surgical site infections which rarely led to device explantations or permanent neurologic consequences. 25-28 Similar results were also found in patients receiving VNS, where the total complication risk amounted to 3.7% with most being infections, hematomas, and vocal cord palsies. 29 In patients who underwent open resection, as determined by a nationwide study on over 6000 patients, a 30-day mortality rate of 3.4% and a complication rate of 17.9% were recorded.…”
Section: Discussionsupporting
confidence: 63%
“…Neuromodulation strategies vary based on the patient seizure type and frequency, including those that target the SOZ and those that target neural networks associated with seizure propagation [16][17][18]. There are currently three types of devices: vagus nerve stimulation (VNS), deep brain stimulation (DBS), and RNS [19,20].…”
Section: Common Neuromodulation Techniquesmentioning
confidence: 99%
“…While subcortical areas are less studied and understood than the cortex in epilepsy, recent research has shown that they may play a more significant role in some types of epilepsy than previously thought [ 9 ]. For example, some types of focal epilepsy, which originate in a specific area of the brain, may involve subcortical structures in addition to the cortex [ 10 ]. According to the focus and spread of discharges, unprovoked recurrent epileptic seizures may be classified as generalized, focal, and epileptic spasms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%